Flexible DNA junction assisted efficient construction of stable gene nanoparticles for gene delivery. Issue 9 (21st December 2015) - Liu, Jianbing; Li, Yanyan; Ma, Dejun; Ouyang, Di; Xi, Zhen
Abstract : A flexible DNA junction was designed to construct stable gene nanoparticles, which can be used as efficient gene cargo for eukaryotic cells. Abstract : A flexible DNA junction was designed to assist the construction of stable gene nanoparticles with multiple target gene copies, which can be used as efficient gene cargo with successful expression in eukaryotic cells for gene delivery.